The symptom network of internet gaming addiction, depression, and anxiety among children and adolescents - Yuntian Xie; Lu Tang (Scientific Reports)
Abstract Internet gaming addiction (IGA), depression, and anxiety are significant issues among children and adolescents, with substantial social implications. Understanding the specific characteristics of this relationship is crucial for developing effective prevention and intervention strategies. The present study employed network analysis to explore the symptom network of IGA, depression, and anxiety among 1,548 Chinese children and adolescents. The results showed that the core symptoms of IGA among children and adolescents were “tolerance”, “withdrawal”, and “conflict”. There was no significant gender difference in the structure, global strength, and core symptoms of IGA. Although there were no significant differences in the structure of the symptom network of IGA among children and adolescents of different ages, there were significant differences in global strength and some core symptoms (“conflict”). The core symptoms of the comorbidity of IGA, depression, and anxiety in children and adolescents included “feeling downhearted and blue”, “breathing difficulty”, “difficult to work up the initiative to do things”, and “withdrawal”. The comorbidity network did not show significant gender and age differences in network structure, but there were significant gender differences in global strength. Furthermore, there were significant gender and age differences in some core symptoms. The social impact of these findings is profound, highlighting the need for targeted interventions in schools and communities to address IGA and its comorbidities. Our results also suggest that interventions should be tailored to consider gender and age differences to maximize effectiveness.